APLIKASI BUNGA TULIP SEBAGAI UNSUR DEKORATIF PADA ALMARI PAKAIAN - Nita Coviana; Jati Widagdo (SULUH: Jurnal Seni Desain Budaya, 2019)
The use of Jepara ornaments is intended, so that Indonesian furniture designers should still care about the arts and culture of the archipelago, namely by applying handicraft products into them, so that they can become a media of socialization and appreciation of Indonesian culture.Many activities are carried out on the terrace, so humans will need facilities to support these activities, namely chairs and tables. Humans need a table and chairs design that can support all their activities on the terrace.The combination of wood and stainless materials is an option in making patio chairs and tables, with a simple design, which is one of the products that humans need for their patio space. Chair and table designs can be placed in any type of terrace, creative and new designs make these chairs and tables a point of interest on the terrace